Child Labor, Well-Being, and Academic Performance: Examining the Role of Work Experience Among Senior High School Learners - Colina, Dundee (Journal of Interdisciplinary Perspectives, 2025)
Child labor remains a pressing global issue, with approximately 160 million children affected in 2020 (UNICEF & ILO, 2021), including many adolescents in Tanjay City and Pamplona, Philippines, compelled by poverty into hazardous forms of work. This study investigates how work experience relates to academic performance and workplace well‑being among senior high school students aged 16 to 17 engaged in labor covered by ILO Convention No. 138. Employing a descriptive, comparative, and correlational design, purposively selected respondents working in agriculture, domestic service, and multiple sectors were assessed using ANOVA, Kruskal‑Wallis tests, and Pearson correlation. The most prevalent form of child labor was farming. Despite limited exposure to severe labor abuses, participants maintained satisfactory academic performance. Overall workplace well‑being scores were high, especially in the domains of meaning, mindset, and engagement. Student workers in domestic roles reported the lowest levels of well‑being, whereas those combining multiple forms of work reported the highest. Work experience duration was positively and significantly associated with overall well-being, and specific domains, physical health, and engagement, demonstrated significant positive associations with academic success. Findings highlight the complex relationship between academic performance and work conditions, showing resilience among youth despite challenging circumstances. These results have important implications for interventions, indicating a need for programs that extend beyond physical safety to include psychosocial support and flexible educational arrangements. Future research employing longitudinal and cross-contextual designs is essential to understand further how work experience shapes well-being and academic outcomes among working youth.